2022
DOI: 10.31083/j.jomh1807157
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Variations Accumulated Workload and Sprint Performance in Elite Adolescent Soccer Players

Abstract: Background:The aim of this study is to analyze the relationship between the accumulated training load parameters (i.e., acute (AWL), chronic (CWL), acute: chronic workload ratio (ACWR), training monotony (TM), and training strain (TS)) and sprint performance variations in elite adolescent soccer players, taking into account the maturation status of the players. Besides, we aimed to use regression models with mentioned parameters, sprint level, and peak height velocity (PHV) as predictors to explain variations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 64 publications
1
2
0
Order By: Relevance
“…During the five weeks of the pre-season phase, the accumulated ITI (average accumulated weeklyITI: 2439.9 ± 224.7 a.u.) were similar to those reported for professional senior soccer players [35,36], but higher than those reported for junior soccer players [23,37]. Significant week-to-week changes in average weekly ITI (0.5 to 26%) were determined between weeks (Table 2), indicating that there was progression in the stimulus, as well as inter-week variability.…”
Section: Discussionsupporting
confidence: 77%
“…During the five weeks of the pre-season phase, the accumulated ITI (average accumulated weeklyITI: 2439.9 ± 224.7 a.u.) were similar to those reported for professional senior soccer players [35,36], but higher than those reported for junior soccer players [23,37]. Significant week-to-week changes in average weekly ITI (0.5 to 26%) were determined between weeks (Table 2), indicating that there was progression in the stimulus, as well as inter-week variability.…”
Section: Discussionsupporting
confidence: 77%
“…Considering CW and AW, higher values were found in the 1 st half of the season, followed by higher values of DOMS compared to the importance of the 2 nd season. A previous study on U16 players also found higher values of ACWLR in the early season [33]. However, a prior survey of U16 players showed that higher values for CW were found at the season's end [34].…”
Section: Discussionmentioning
confidence: 75%
“…A study of 11- to 15-year-olds discovered that peak height occurred between 13 and 14 and coincided with peak aerobic capacity, speed, and agility [ 42 ]. However, in similar studies, researchers showed that the peak of power growth occurs between the ages of 15 and 16 [ 43 , 44 ]. So, based on the mentioned data, we chose this age range as the selection criterion based on the above statistics.…”
Section: Discussionmentioning
confidence: 99%